NOTES ON A COLLECTION OF DRAGONFLIES (ORDER ODONATA) FROM. THE DUTCH EAST INDIES AND DESCRIPTIONS OF FOUR NEW SPECIES FROM THE NEIGHBOURING CONTINENT - F C FRASER (Research Center for Biology, 1926)
abstract not avaialable